113k views
2 votes
Solve 4n+2mn=3mn ² for m.

User Angelous
by
5.6k points

1 Answer

4 votes

Answer:

m = sqrt(4/(3 n) + 1/(9 n^2)) + 1/(3 n) or m = 1/(3 n) - sqrt(4/(3 n) + 1/(9 n^2))

Explanation:

Solve for m:

4 n + 2 m n = 3 m^2 n^2

Subtract 3 m^2 n^2 from both sides:

4 n + 2 m n - 3 m^2 n^2 = 0

Divide both sides by -3 n^2:

m^2 - 4/(3 n) - (2 m)/(3 n) = 0

Add 4/(3 n) to both sides:

m^2 - (2 m)/(3 n) = 4/(3 n)

Add 1/(9 n^2) to both sides:

m^2 + 1/(9 n^2) - (2 m)/(3 n) = 4/(3 n) + 1/(9 n^2)

Write the left hand side as a square:

(m - 1/(3 n))^2 = 4/(3 n) + 1/(9 n^2)

Take the square root of both sides:

m - 1/(3 n) = sqrt(4/(3 n) + 1/(9 n^2)) or m - 1/(3 n) = -sqrt(4/(3 n) + 1/(9 n^2))

Add 1/(3 n) to both sides:

m = sqrt(4/(3 n) + 1/(9 n^2)) + 1/(3 n) or m - 1/(3 n) = -sqrt(4/(3 n) + 1/(9 n^2))

Add 1/(3 n) to both sides:

Answer: m = sqrt(4/(3 n) + 1/(9 n^2)) + 1/(3 n) or m = 1/(3 n) - sqrt(4/(3 n) + 1/(9 n^2))

User Oded Niv
by
5.2k points